High-Fat Diet Increased Oxidative Stress and Mitochondrial Dysfunction Induced by Renal Ischemia-Reperfusion Injury in Rat - Prem, Priyanka N.; Kurian, Gino A. (Frontiers in Physiology, 2021)
Renal ischemia-reperfusion (IR) injury is one of the major causes of acute kidney injury influenced by the ischemic duration and the presence of comorbidities. Studies have reported that high-fat diet consumption can induce renal lipotoxicity and metabolic dyshomeostasis that can compromise the vital functions of kidney. This study aimed to evaluate the impact of a high-fat diet in the recovery of renal tissue from IR and explored the cellular pathology. In this study, 24 male Wistar rats were divided into two groups: normal diet (ND; n = 12) and high-fat diet (HD; n = 12), which were further subdivided into sham and IR groups at the end of the dietary regimen. The high-fat diet was introduced in 4-week-old rats and continued for 16 weeks. IR was induced by bilateral clamping of the renal peduncle for 45 min, followed by 24 h of reperfusion. Blood chemistry, estimated glomerular filtration rate (eGFR), mitochondrial function, and oxidative stress analysis were carried out to study the pathological changes. The rats fed with HD showed a decreased eGFR and elevated plasma creatinine, thereby compromised kidney function. Subcellular level changes in HD rats are deceased mitochondrial copy number, low PGC-1α gene expression, and declined electron transport chain (ETC) enzymes and adenosine triphosphate (ATP) level. Upon IR induction, HD rats exhibited severely impaired renal function (eGFR-0.09 ml/min) and elevated injury markers compared with ND rats. A histological analysis displayed increased tubular necrosis and cast formation in HD-IR in comparison to ND-IR. The oxidative stress and mitochondrial dysfunction were more prominent in HD-IR. In vitro protein translation assessment revealed impaired translational capacity in HD-IR mitochondria, which suggests mitochondrial changes with diet that may adversely affect the outcome of IR injury. High-fat diet consumption alters the normal renal function by modifying the cellular mitochondria. The renal changes compromise the ability of the kidney to recover from ischemia during reperfusion.